Deliberation in Bazargan’s Thought - Maryam Mir Mohammad Sadeghi (پژوهشهای حقوقی)
“Deliberation” in Mehdi Bazargan’s thought, in changeable issues, is based on contemporary reason. But on the one hand, both deliberation and contemporary human reason cannot ignore the general approaches of »religion«, and on the other hand, distinguishing the religious general approaches without using »reason« cannot become possible. While »reason« is the reference for picking methods, it is the basis for understanding religion. Accordingly, reason and religion are not separate from each other. In fact, »deliberation« in Bzargan’s thought is a clear example of the accompaniment of reason and religion. To demonstrate this proposition, the bases for »deliberation« in Bazargan’s thought will be considered in three parts: the principle of deliberation in government; the principle of revelatory prophecy; secularization of government or separation of religion and government, not separation of religion and politics; and the differentiation between values and methods. Based on these three principles, we can speak of the originality of both »religion« and »reason« in Bazargan’s thought.Bazargan's experience after the 1957 Revolution, which faced him with the real problem of governing, became a means of gradual changes in his thoughts than his combative approach in the 1340s and 1350s. These gradual changes limit Islam's position from the pervasive ideology with a lot of commands for all social and political programs to merely directing ideology in a set of principles and generalities. Therefore, the scope of deliberation, which was limited to executive affairs in his thoughts before the revolution, extends to the legislative domain, which this article attempts to discuss in detail.